Merancang Proses Menentukan Keperluan Latihan Bagi Staf Akademik Kolej Profesional MARA - Anida Ismail (Universiti Sains Islam Malaysia, 2024)
Conducting the Training Needs Analysis (AKL) becomes the initial process of determining the training needs of an institution . The process for conducting Training Needs Analysis in detail, is to analyze the three main forms such as Organizational Analysis, Job Analysis and Analysis of Labor. The current study used ’mixed method’ approach that uses ’explanatory research’approach which collected data from various methods of explanation. In this study, the main design was quantitative method and supported with qualitative method. Data from questionnaires show that the emphasis given by the MARA Training Management towards the three analysis were on High Range with the lowest mean value on the analysis of employees. Data from interviews show that MARA Training Management did not conduct the analysis clearly. In conclusion, MARA Training Management has given less emphasis on conducting the analysis before determining which training will be given to the academic staff. Thus, the implications of this study showed the need for the MARA Training Management to conduct Training Needs Analysis systematically in order to identify appropriate training for MARA Professional College’s academic staff.